PkM Peningkatan Nilai-Nilai Pendidikan Karakter dalam Kegiatan Belajar Mengajar di Pesantren Mizanul Ulum Sanrobone Takalar - Surani, Surani; Darmawangsa, Andi; Ardi, Ardi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The main purpose of the Community Service Activity (PKM) is to make a significant contribution to strengthening the character of teachers in the environment of Mizanul Ulum Sanrobone Islamic Boarding School, Takalar. The specific focus on "Strengthening Character Education" indicates that the activity aims to enhance the understanding and application of character values among boarding school teachers. Methodology: The implementation of this Community Service Activity (PkM) is carried out in several stages. First, a deep identification is conducted on the core values of character education that are the focus of improvement in the learning environment of Pesantren Mizanul Ulum Sanrobone Takalar. Results: The results of this Community Service Activity (PkM) not only serve as a starting point in improving teachers' understanding of character education concepts but also create a foundation for the implementation of character values in everyday learning. Through a quantitative approach, we can clearly observe positive changes in the understanding, attitudes, and willingness of the teachers. Limitations: The scope of this activity is limited to Mizanul Ulum Sanrobone Islamic Boarding School, Takalar. Therefore, the results may not be directly applicable to other boarding schools or different educational contexts. The research was conducted within a specific time frame, potentially limiting the ability to fully capture long-term changes. Contribution: This activity makes a significant contribution to strengthening the character of boarding school teachers, establishing a foundation for the implementation of character values in the curriculum and daily activities. The implementation plan derived from this activity serves as a guideline for teachers, providing practical guidance for integrating character education within the boarding school context.